Herbstprognose der schweizerischen Gesundheitsausgaben 2008-2011 - Martin Straub; Jochen Hartwig (ETH Zurich, KOF Swiss Economic Institute, 2009)
The autumn forecast for Swiss health expenditure covers the years 2008 to 2011 (official data range to 2007). For the year 2008, the forecast assumes a higher-than-average growth in health expenditure. While a still solid growth is expected for the year 2009, a cooling down as a consequence of the recession is predicted for the years 2010 and 2011. The growth in the year 2010 is further slowed down by price cuts for pharmaceuticals.
Keywords: 330; Gesundheitskosten; Prognose; Prognoseverfahren; Schweiz